Application of an immunoglobulin Y-alkaline phosphatase bioconjugate as a diagnostic tool for influenza A virus - Ozkan, Busra; Budama-Kilinc, Yasemin; Cakir-Koc, Rabia; Mes, Sevim; Badur, Selim (TAYLOR & FRANCIS INC, 2019)
The diagnosis of influenza A virus is essential since it can be confused with influenza A like illness and lead to inaccurate drug prescription. In this study, the M2e peptide, a strategic antigen that is conserved in all virus subtypes, was used as a diagnostic marker of influenza A. For the first time, M2e-specific IgY antibody was covalently conjugated to alkaline phosphatase (ALP) enzyme in the presence of glutaraldehyde. The antibody-enzyme bioconjugate was characterized by fluorescence and Fourier-transform infrared spectroscopy. Subsequently, the diagnostic value of this bioconjugate was evaluated by direct sandwich ELISA using nasopharyngeal swab samples positive/negative for H1N1 and H3N2, which were previously analyzed by rRT-PCR for influenza. In conclusion, the M2e-specific IgY-ALP bioconjugate demonstrated positive results for Influenza A in samples that were diagnosed as Influenza A via the RT-PCR method.
Keywords: Immunoglobulin Y; influenza A; alkaline phosphatase; ELISA methods; diagnosis; LINKED-IMMUNOSORBENT-ASSAY; MONOCLONAL-ANTIBODY; MATRIX PROTEIN-2; M2 PROTEIN; VACCINE; GENERATION; ECTODOMAIN; FORM; IGY; Biotechnology & Applied Microbiology